2022
DOI: 10.52380/ijpes.2022.9.3.626
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Grit Scale: Test of Measurement Invariance across University and High School Students

Abstract: The concept of grit has becomea widely investigated topic in mental health and education in recent years. This study aims to develop a tool for measuring grit in high school and university students and to examine the measurement invariance of the developed scale on two different groups. A total of 586 high school students (411 female, 70%; 175 male, 30%) and 639 (437 female, 63%; 202 male, 37%) university students participated in the study. Grit Scale, Short Grit Scale, and Beck Hopelessness Scale were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…To date, several researchers (Adanır et al, 2023;Fletcher et al, 2023;Schina et al, 2021) have provided an outlook on the factors that contribute to the significantly better performance of educational robots. Insights into this outlook were gained through the adoption of the multidimensional grit scale framework proposed by Kardas et al (2022). Among the three scales measuring students' grit, such as perseverance, commitment to goals, and consistency of interest, it was observed that students in the EG demonstrated significantly higher scores.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, several researchers (Adanır et al, 2023;Fletcher et al, 2023;Schina et al, 2021) have provided an outlook on the factors that contribute to the significantly better performance of educational robots. Insights into this outlook were gained through the adoption of the multidimensional grit scale framework proposed by Kardas et al (2022). Among the three scales measuring students' grit, such as perseverance, commitment to goals, and consistency of interest, it was observed that students in the EG demonstrated significantly higher scores.…”
Section: Discussionmentioning
confidence: 99%
“…Grit scale. Kardas ¸et al (2022) developed the grit scale specifically for high school and university students and investigated the scale's measurement invariance across these two groups. The exploratory factor analysis identified a 14-item scale comprising three sub-dimensions: perseverance, commitment to goals, and consistency of interest.…”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations